Imaging Outcomes of Emergency MRI in Patients with Suspected Cerebral Venous Sinus Thrombosis: A Retrospective Cohort Study - Happonen Tatu; Nyman Mikko; Ylikotila Pauli; Kytö Ville; Laukka Dan; Mattila Kimmo; Hirvonen Jussi (MDPI, 2025)
Cerebral venous sinus thrombosis (CVST) is a rare neurological emergency condition with non-specific symptoms. Imaging options to rule out CVST are computed tomography (CT) and magnetic resonance imaging (MRI). This study aimed to determine the imaging outcomes of emergency MRI as a first-line imaging method in patients with suspected CVST. In this retrospective cohort study, we analyzed emergency brain MRI referrals from a five-year period in a tertiary hospital for suspicion of CVST. We recorded patient characteristics, risk factors mentioned in the referrals, and imaging outcomes. Altogether 327 patients underwent emergency MRI on the grounds of suspected CVST. MRI showed evidence of CVST among five patients (1.5%). Imaging showed other clinically significant pathology in 15% of the patients and incidental findings in 5% of the patients. Despite clinical suspicion, the diagnostic yield of emergency MRI for CVST is low and similar to that previously reported for CT. MRI is an alternative imaging method devoid of ionizing radiation in patients with suspected CVST.